Integrated Omics Analysis Reveals Alterations in the Intestinal Microbiota and Metabolites of Piglets After Starvation - Ma, Yijia; Lu, Chang; Ji, Bingzhen; Qin, Junjun; Cai, Chunbo; Yang, Yang; Zhao, Yan; Liang, Guoming; Guo, Xiaohong; Cao, Guoqing; Li, Bugao; Gao, Pengfei (Frontiers in Microbiology, 2022)
Obesity is a serious public health problem. Short-term starvation is an effective way to lose weight but can also cause harm to the body. However, a systematic assessment of the relationship between the intestinal microbiota and metabolites after complete fasting is lacking. Pigs are the best animal models for exploring the mechanisms of human nutrition digestion and absorption, metabolism, and disease treatment. In this study, 16S rRNA sequencing and liquid chromatography-mass spectrometry were used to analyze the changes in the intestinal microflora and metabolite profiles in piglets under starvation stress. The results showed that the microbial composition changed significantly in the starvation groups compared to that of the control group (P < 0.05), suggesting that shifts in the microbial composition were induced by starvation stress. Furthermore, differences in the correlation of the intestinal microbiota and metabolites were observed in the different experimental groups. Starvation may disrupt the homeostasis of the intestinal microflora and metabolite profile and affect the health of piglets. However, piglets can regulate metabolite production to compensate the effects of short-term starvation. Our results provide information for exploring the mechanism of diet and short-term hunger for intestinal homeostasis.